ANALISIS PENGARUH VARIABEL MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM LQ45 - Izzatul Aini; Maslichah Maslichah (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research is to analyze the influence of inflation rate,interest rate of Bank Indonesia (BI Rate), and money supply (M2) on stock priceindex LQ45 period January 2015 until December 2016. The method used in thisresearch is multiple linear regression analysis using Statistical Product of ServiceSolution (SPSS). This study shows that simultaneously or together with the inflationrate, the interest rate of Bank Indonesia (BI Rate), and the money supply (M2) havesignificant implications on the LQ45 stock price index in the period of January 2014until December 2016. Then partial inflation rate and money supply (M2) havesignificant negative implications on LQ45 stock price index. Meanwhile, the interestrate of Bank Indonesia (BI Rate) has a significant positive implication on LQ45 stockprice index.Keywords: LQ45 stock price index, inflation rate, Bank Indonesia rate (BI Rate), andmoney supply (M2).